A holistic approach to Henry Peach Robinson's "Fading Away" for a medical humanities class - Lota, Manpreet; Divaker, Shraya; Dubey, Arun Kumar; Bhat, Malpe Surekha (Research and Humanities in Medical Education, 2020)
Henry Peach Robinson's "Fading away" can be interpreted either through a reductionist approach or a holistic approach. He perfected this fictional photograph through five negatives to create an anecdote and change attitudes towards tuberculosis. While there are many interpretations of this piece of art from a reductionistic approach "literary, artistic, humanistic, or illness-narrative" there are hardly any from a holistic perspective integrating all these angles. When used during a medical humanities course, the photograph provoked students to think beyond the purely artistic and the purely medical aspects of disease. Some of the messages that medical students took home were: 'grief could be experienced by anyone'; 'love expands into diverse manifestations during times of sadness; 'we must empathize with others and what they go through'. This paper reports on our attempt to adopt a holistic approach to analyze the photograph from Robinson's perspective and with respect to modern medicine.